2019
DOI: 10.1055/a-0877-7255
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a UHPLC-DAD Method for the Quantitative Analysis of Major Dihydrochalcone Glucosides from Thonningia sanguinea VAHL

Abstract: Thonnigia sanguinea is a plant widely used in traditional African medicine against a variety of diseases. The obligate parasite is growing throughout tropical African forests and utilizes a large variety of hosts. Dihydrochalcone glucoside derivatives isolated from the subaerial parts of this plant were identified as potential antidiabetic lead compounds. In this study, an ultrahigh-performance liquid chromatographic method coupled with a photodiode array detector was developed for the quantitation of six majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Initially, it was thought that the occurrence of dihydrochalcones was limited to only about 30 plant families. With the development of more sensitive analytical methods, it turned out that they are more widespread in nature [25]. The most common methods of dihydrochalcones isolation involve their extraction form leaves using such solvents as ethanol, diethyl ether, methanol, and hexane with dichloromethane or high-pressure extraction with supercritical CO 2 .…”
Section: Dihydrochalcones From Natural Sourcesmentioning
confidence: 99%
“…Initially, it was thought that the occurrence of dihydrochalcones was limited to only about 30 plant families. With the development of more sensitive analytical methods, it turned out that they are more widespread in nature [25]. The most common methods of dihydrochalcones isolation involve their extraction form leaves using such solvents as ethanol, diethyl ether, methanol, and hexane with dichloromethane or high-pressure extraction with supercritical CO 2 .…”
Section: Dihydrochalcones From Natural Sourcesmentioning
confidence: 99%
“…The purity reflects the percentage of the peak area of the target peak vs. the total integration area throughout the chromatogram. The contents of the target compounds (1)-( 4), thA, and thB in the used extract were determined using a validated UHPLC method previously published [7]. Therefore, three solutions of 15 mg defatted MeOH extract in 25 mL MeOH were prepared and subsequently…”
Section: Hplc Analysismentioning
confidence: 99%
“…In a recent study on this plant, we reported the in vitro pharmacological potential of T. sanguinea and some of its secondary metabolites as inhibitors of protein tyrosine phosphatase 1B (PTP1B) [5], a cellular receptor representing a potential target for the treatment of diabetes, obesity, and some types of cancer [6]. The crude methanol (MeOH) extract of the plant batch investigated in the present study contained six dihydrochalcone glucosides as major compounds, which were identified as thonningianin A (thA), thonningianin B (thB), 3- (4) [5,7]. Except for (1), all mentioned compounds comprise galloyl groups or a hexahydroxydiphenoyl group at their glucose moiety and can thus be defined as hydrolysable tannins.…”
Section: Introductionmentioning
confidence: 97%